2019
DOI: 10.1002/jcp.28399
|View full text |Cite
|
Sign up to set email alerts
|

FOXE1 supports the tumor promotion of Gli2 on papillary thyroid carcinoma by the Wnt/β‐catenin pathway

Abstract: Papillary thyroid carcinoma (PTC) is a common malignancy in thyroid tissue. However, the molecular mechanism of PTC tumor progression remains unknown. The hedgehog (Hh) pathway is thought to play a key role during PTC development. Here we investigate the effects of glioma‐associated oncogene protein‐2 (Gli2), an important transcription factor of the Hh‐signaling pathway, on PTC. Gli2 and forkhead box E1 (FOXE1) protein levels were upregulated in tissues of PTC patients and PTC cell lines. Using the PTC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Our analysis of FOXE1 expression in a panel of thyroid cancer cell lines shows that FOXE1 levels inversely correlate with differentiation degree according to histological sub-type origin of cell lines, which is consistent with data on the expression patterns of FOXE1 in PTC and normal tissues by TCGA and fits with data of FOXE1 expression in a genome array of human tumors that include all histological variants (Giordano et al 2006). It should be mentioned that other recent studies have reported overexpression of FOXE1 in PTC samples as well as in K1 and TPC1 cell lines (Ding et al 2019, Ma et al 2019, which contrasts with our data. We do not have an Endocrine-Related Cancer explanation for this apparent discrepancy other than the use of different antibodies in the studies; however, our results showing lower levels of FOXE1 in PTC cells than in control cells are in agreement with data from TCGA on more than 500 samples of patients with PTC.…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis of FOXE1 expression in a panel of thyroid cancer cell lines shows that FOXE1 levels inversely correlate with differentiation degree according to histological sub-type origin of cell lines, which is consistent with data on the expression patterns of FOXE1 in PTC and normal tissues by TCGA and fits with data of FOXE1 expression in a genome array of human tumors that include all histological variants (Giordano et al 2006). It should be mentioned that other recent studies have reported overexpression of FOXE1 in PTC samples as well as in K1 and TPC1 cell lines (Ding et al 2019, Ma et al 2019, which contrasts with our data. We do not have an Endocrine-Related Cancer explanation for this apparent discrepancy other than the use of different antibodies in the studies; however, our results showing lower levels of FOXE1 in PTC cells than in control cells are in agreement with data from TCGA on more than 500 samples of patients with PTC.…”
Section: Discussionsupporting
confidence: 89%
“…As a core protein in Hedgehog (Hh) signaling during tumorigenesis, GLI2 has been shown to be pro-tumorigenic in pancreatic cancer (25), bladder cancer (26), and ovarian cancer (27) amongst others. Additionally, GLI2 was tumor-promoting via FOXE1 in papillary thyroid carcinoma through the Wnt/β-catenin pathway (28). In this study, we found that oncogenic GLI2 was a transcription activator of LMCD1-AS1, supporting its role in THCA regulation.…”
Section: Discussionsupporting
confidence: 58%
“…This tempted us speculating on upregulation of Tf that was confirmed for 44 mRNA versus only 3 mRNA in AS-TEX treated EC. Strongly upregulated ARID3a mRNA promotes IFNα expression [104], BCL11a 1 binds to selective histone subunits, particularly RBP4 [105], FOXE1 together with ETV1 1 promotes telomerase reverse transcription promoter activation [106] and also affects via GLI2 1 Wnt/β-catenin pathway activation [107]. HES7 is best known for its dominant role in somitogenesis with synergistic signaling including TBX6 1 and Notch [108].…”
Section: The Ec Response To Tex: Signaling Cascade Activation and Nucmentioning
confidence: 99%